Facial nodular fasciitis in an adult patient: a case report of an uncommon manifestation - Rodrigues-Fernandes, Carla Isabelly; Souza, Roberta Karolina Borges de; Bezerra, Hélen Kaline Farias; Carvalho, Elaine Judite de Amorim; Vargas, Pablo Agustin; Perez, Danyel Elias da Cruz (Journal of Oral Diagnosis, 2025)
Nodular fasciitis is a pseudosarcomatous, self-limited lesion composed of fibroblasts and myofibroblasts. Craniofacial lesions are more common in pediatric patients. This report presents a rare case of nodular fasciitis involving the face of an adult patient. A 32-year-old woman presented with a painless subcutaneous mass at the right zygomatic region, with one year of duration. The diagnostic hypotheses were epidermoid cyst and neurofibroma. An excisional biopsy was performed, and the microscopic examination exhibited an admixture of spindle-shaped cells and acellular areas associated with prominent collagen bands. No cellular atypia was observed. Immunohistochemical findings demonstrated positivity for alpha-SMA, HHF35, and beta-catenin. Tumor cells were negative for STAT6. The final diagnosis was nodular fasciitis. The patient has not presented any recurrences so far. Clinicians and pathologists must be capable to distinct nodular fasciitis and malignant tumors to avoid misdiagnosis and overtreatment.